Penggunaan QRIS di Kalangan UMKM (Studi Persepsi dan Intensi UMKM di Kota Pekalongan) - Muhammad Ariful Amar; Defta Nasya Berliani; Dewi Dwi Marta; Sabrina Diva Nur Rahmadani; Wafiq Alizar Rahma (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to analyze the perception and intensity of use of QRIS (Quick Response Code Indonesian Standard) among MSMEs (Micro, Small, and Medium Enterprises) in Pekalongan using descriptive qualitative research methods. QRIS is an electronic payment system that allows MSMEs to receive payments via QR codes that can be scanned using a banking application or digital wallet. Through a descriptive qualitative approach, this study involved in-depth interviews with MSMEs owners and managers in Pekalongan to understand their perceptions of QRIS and their intentions in using this payment system. The researcher will use a structured interview guide to collect data on the knowledge, experience, and attitude of MSMEs towards QRIS. Data collected from interviews will be analyzed using descriptive analysis techniques, where findings and patterns arising from interviews will be identified, grouped, and interpreted. This analysis will provide a more in-depth insight into the perception and intensity of QRIS use among MSMEs in Pekalongan City. The results of this study are expected to provide a more in-depth understanding of the factors affecting QRIS adoption among MSMEs from their own perspective. The resulting information can be used to develop better strategies and policies in promoting QRIS use among MSMEs. In addition, the results of this study can also provide valuable input for banks, governments, and other stakeholders in expanding QRIS adoption and increasing financial inclusion in the MSME sector in Pekalongan City. It is hoped that this study will contribute significantly to the development and further understanding of QRIS implementation among MSMEs and help create a more efficient and inclusive payment ecosystem for MSMEs in Pekalongan City and the community as a whole.